Towards the new and next normal: A study on business resilience and virtual event strategies for event success of three selected event companies in Metro Manila amidst the COVID-19 pandemic - Besares, Ly-or Thomas Goce (Animo Repository, 2022)
Events are deemed an important part of human life. The onset of the COVID-19 pandemic has brought changes to the events industry both locally and internationally, impacting the capacity of several events companies. The challenge of the pandemic has forced industry transformation -- with event companies transitioning to virtual events as an alternative for in-person events. This research paper is a multiple case study of Partyforum Events and Marketing, Ingenio Creatives Advertising Corp., and 4.0 MANAGEMENT. A triangulation method consisting of individual interviews with company representatives, focus group discussions with various event stakeholders, and individual interviews with industry experts was used to explore the strategies that have allowed these companies to stay resilient and successfully organize virtual corporate events despite the ongoing pandemic The data gathering and analysis procedures were patterned with the case study methodology of Yin (2003). The findings revealed that the following are effective strategies for achieving event success: 1) forming connections, 2) adaptability and learning, 3) boost in-person confidence, 4) pre-planning and planning, 5) interactive events, 6) topic and content, 7) evaluation, and 8) privacy and security. A detailed discussion on what these strategies are and how they lead to the successful implementation of events are presented in this paper.